Ask, don't tell; A complex dynamic systems approach to improving science education by focusing on the co-construction of scientific understanding. (April 2017) - van Vondel, Sabine; Steenbeek, Henderien; van Dijk, Marijn; van Geert, Paul
Abstract: Studying real-time teacher-student interaction provides insight into student's learning processes. In this study, upper grade elementary teachers were supported to optimize their instructional skills required for co-constructing scientific understanding. First, we examined the effect of the Video Feedback Coaching intervention by focusing on changes in teacher-student interaction patterns. Second, we examined the underlying dynamics of those changes by illustrating an in-depth micro-level analysis of teacher-student interactions. The intervention condition showed significant changes in the way scientific understanding was co-constructed. Results provided insight into how classroom interaction can elicit optimal co-construction and how this process changes during an intervention. Highlights: A Video Feedback Coaching intervention for elementary teachers was implemented. We studied the characteristics of real-time teacher-student interactions. We focused on teacher-student co-construction of scientific understanding. Changes were found in the process of co-construction in the intervention condition. No changes were found in classrooms of the control condition.